2021
DOI: 10.1371/journal.pgen.1009688
|View full text |Cite
|
Sign up to set email alerts
|

Rubicon prevents autophagic degradation of GATA4 to promote Sertoli cell function

Abstract: Autophagy degrades unnecessary proteins or damaged organelles to maintain cellular function. Therefore, autophagy has a preventive role against various diseases including hepatic disorders, neurodegenerative diseases, and cancer. Although autophagy in germ cells or Sertoli cells is known to be required for spermatogenesis and male fertility, it remains poorly understood how autophagy participates in spermatogenesis. We found that systemic knockout mice of Rubicon, a negative regulator of autophagy, exhibited a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…On the basis of used gene-targeting strategies, only the mouse line used in this study was deficient in the expression of RUBCN 130 but not that of RUBCN 100 . Previous studies using this line have shown that RUBCN 130 deficiency in mouse models leads to enhanced autophagic flux in various cell types ( 12 , 14 , 15 , 17 , 18 ). However, the loss of both RUBCN isoforms does not enhance autophagic flux but rather impairs LAP/LANDO ( 19 , 20 , 22 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the basis of used gene-targeting strategies, only the mouse line used in this study was deficient in the expression of RUBCN 130 but not that of RUBCN 100 . Previous studies using this line have shown that RUBCN 130 deficiency in mouse models leads to enhanced autophagic flux in various cell types ( 12 , 14 , 15 , 17 , 18 ). However, the loss of both RUBCN isoforms does not enhance autophagic flux but rather impairs LAP/LANDO ( 19 , 20 , 22 ).…”
Section: Discussionmentioning
confidence: 97%
“…RUBCN deficiency in several cell types enhances autophagy and ameliorates nonalcoholic fatty liver, age-associated disorders such as interstitial fibrosis in the kidney, α-synuclein accumulation in the brain, systemic fat atrophy, osteoporosis, and myocardial ischemia/reperfusion injury (12)(13)(14)(15)(16). However, this deficiency induces metabolic syndrome (17) and suppresses Sertoli cell function (18) in mouse models. RUBCN also regulates a noncanonical autophagic process called LC-3-associated phagocytosis (LAP), LC-3-associated endocytosis (LANDO), or micropinocytosis (LAM) (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that the changes in gene expression signatures were closely related to the function of specific cell types. For example, the expression of GATA4, a TF that is essential for Sertoli cell function, 70,71 was increased in Sertoli cells at E125. The expression of genes associated with sterol biosynthetic and metabolic processes, such as CYP11A1, STAR, and CYP51A1, was increased in Leydig cells at E125.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has identified that Rubicon affects male fertility: Rubicon deficiency in Sertoli cells causes defective spermatogenesis via accelerated autophagic degradation of GATA4, which is an essential transcription factor for Sertoli cell function ( Yamamuro et al, 2021 ). This report is interesting from the viewpoint of ageing: it has been previously known that there is a negative correlation between fertility and longevity, although the causal relationship has been unclear ( Partridge et al, 2005 ; Kenyon, 2010 ).…”
Section: Ageing and Rubiconmentioning
confidence: 99%